Pertanggungjawaban Perdata Bagi Pelaku Pelanggaran Kekayaan Intelektual dalam Era Digital - Komang Adi Utama Putra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The digital age has brought significant changes in the protection of intellectual property rights (IPR), making it increasingly crucial to safeguard works and innovations from easy infringement. This research aims to analyze the civil liability for IPR infringers in the digital era, which involves the application of civil law principles such as the elements of fault, presumption of liability, and absolute liability. IPR regulations in Indonesia have evolved since the Dutch colonial period until now, adjusting to digital dynamics through various new laws and regulations. This research uses normative methods supported by empirical methods to analyze in depth the civil liability for perpetrators of intellectual property rights (IPR) infringement in the digital era. This approach allows researchers to evaluate legal principles and applicable regulations, as well as collect primary data from real cases, such as copyright infringement on online platforms. Analysis of empirical data from infringement cases provides tangible evidence of the application of the law and its impact. Thus, normative methods supported by empirical methods provide not only a strong theoretical foundation but also a practical context for more effective policy recommendations in protecting IPR.The case studies show that copyright owners can file a lawsuit and, if proven, perpetrators can be penalized to pay damages as well as court costs. Registration of IPRs provides legal certainty and strong evidence in court. Therefore, preventive legal protection through strict regulation and repressive legal protection through strict sanctions are essential to enforce IPR and prevent further infringement in the digital age. This study concludes that consistent law enforcement and increasing public awareness of the importance of IPR protection are crucial steps in facing the challenges of the digital era.